Analisis Strategi Pemasaran Jamur Rimba Jaya Mushroom - Arminsyurita Arminsyurita (Institut Ilmu Sosial dan Manajemen STIAMI, 2014)
Rimba Jaya Mushroom as companies engaged in the agribusiness industry in the procurement of vegetables and mushrooms to face the problem: unmet demand, the capacity of the products that do not satisfy the market demand and competition from companies that must be observed. Therefore, companies need a strategic move to float the mushroom’s business in order to seize the opportunities facing the problem that continuity and corporate objectives can be achieved. This study aims to identify factors internal environment (Strengths, -Weakness) and external environmental factors (Opportunities-Threats) that affect marketing company, and analyze marketing strategies of Rimba Jaya Mushroom. Based on the results of the SWOT matrix analysis charts and diagrams IE the company's marketing strategy can be recommended Rimba Jaya Mushroom, among others, by taking market share for market penetration at competitive prices, concentration through backward integration is to establish relationships with suppliers, fore the concentration through integration with how to take over the function of the overall distribution, concentration through horizontal integration with a collaborative effort with the work on the market continues to foster relationships with several similar companies that are members of the association of Mushroom’s Company that exist or may hold a joint venture with the company.